2021
DOI: 10.1155/2021/6194806
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Analgesia Effect after Ultrasound-Guided Laparoscopic Renal Surgery

Abstract: Kidney surgery involves placing the kidney in the iliac fossa of the lower abdomen on the right or left side. Studies have found that most kidney patients experience moderate to severe pain after surgery. The stress response caused by postoperative pain, especially visceral pain, not only aggravates the patient’s pain and irritability and aggravates the original complications but may also harm the early recovery of renal function and affect the survival of the kidney. Therefore, adequate postoperative analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Earlier studies indicated that PVB shows a significant analgesic effect for many surgical procedures; especially cardiothoracic surgery, breast surgery, and inguinal hernia repair ( 9 11 ). The application of PVB in renal surgery has been reported recently, and some studies have shown that PVB can effectively control the pain after renal surgery and reduce anesthetic-related complications ( 12 ). Therefore, the purpose of this study is to evaluate the effect of PVB on pain management after renal surgery and provide a reference for the selection of analgesic methods after renal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies indicated that PVB shows a significant analgesic effect for many surgical procedures; especially cardiothoracic surgery, breast surgery, and inguinal hernia repair ( 9 11 ). The application of PVB in renal surgery has been reported recently, and some studies have shown that PVB can effectively control the pain after renal surgery and reduce anesthetic-related complications ( 12 ). Therefore, the purpose of this study is to evaluate the effect of PVB on pain management after renal surgery and provide a reference for the selection of analgesic methods after renal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 min, an appropriate type of DLT was selected, and the anaesthesia intubation operation was performed by an anaesthesiologist with the same amount of experience. In the experiment, intermittent positive pressure ventilation, tidal volume 8 ml/kg, frequency 12 times/min, inspiratory ratio 1 : 2, maintained P ET CO 2 35-40 mm Hg, inhaled 1.5-2.0% sevoflurane during the operation, and pumped remifentanil and propofol were used to maintain an anaesthesia depth BIS of between 45 and 60 [9][10][11].…”
mentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Evaluation of Analgesia Effect after Ultrasound-Guided Laparoscopic Renal Surgery” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%